2020
DOI: 10.3390/jcm9051569
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Injury Patterns in Electric-Scooter Related Accidents—A Prospective Two-Center Report from Germany

Abstract: Since the introduction of rental E-scooters in Germany in mid-June 2019, the safety of this new means of transport has been the subject of extensive public debate. However, valid data on injuries and usage habits are not yet available. This retrospective two-center study included a total of 76 patients who presented to the emergency department following E-scooter-related accidents. The mean age was 34.3 ± 12.4 years and 69.7% of the patients were male. About half of the patients were admitted by ambulance (42.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
97
3
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(130 citation statements)
references
References 19 publications
18
97
3
12
Order By: Relevance
“…Most emergency department presentations were observed in the evening hours (61%). These results are in line with those published in recent literature in which 60 to 65% of accidents were produced during the late evening hours [ 10 , 22 ]. Trivedi et al reported injuries produced from 3 pm to 11 pm in some 56% of the cases [ 5 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Most emergency department presentations were observed in the evening hours (61%). These results are in line with those published in recent literature in which 60 to 65% of accidents were produced during the late evening hours [ 10 , 22 ]. Trivedi et al reported injuries produced from 3 pm to 11 pm in some 56% of the cases [ 5 ].…”
Section: Discussionsupporting
confidence: 93%
“…That fact along with the scarce data published on e-scooter injuries supports them being treated as high-energy mechanisms that can result in severe injuries. These results are in line with those published by Ishmael et al and Störmann et al in which 27.6% of injuries were treated surgically [ 3 , 10 ]. It is important that riders understand the hazards associated with moving around on a two-wheeled vehicle that may reach 30 km/h.…”
Section: Discussionsupporting
confidence: 93%
“…Although trauma caused by e-scooters is poorly described in the literature, recently there has been an increased number of scientific publications on e-scooter–related injuries. 1 , 2 , 3 , 4 , 5 , 6 Most published articles were retrospective observational studies from the United States.…”
Section: Discussionmentioning
confidence: 99%
“…E-scooter services are primarily utilized for recreational purposes [13]. In Austin, TX, our spatial analysis showed that E-scooter usage is concentrated in the downtown and university campus areas [9].…”
Section: Literature Reviewmentioning
confidence: 85%
“…In contrast to the amount of shared micro-mobility research on travel behaviors, there is scarce literature on E-scooter safety due to the lack of data. Although researchers have used survey-based methods [13] and data mining techniques [2] to identify scooter-related injuries and crashes, it is difficult for planners to contextualize the safety issues without sufficient empirical evidence.…”
Section: Introductionmentioning
confidence: 99%